1993
DOI: 10.1007/bf02536059
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerol structure of human colostrum and mature milk

Abstract: Because triacylglycerol (TAG) structure influences the metabolic fate of its component fatty acids, we have examined human colostrum and mature milk TAG with particular attention to the location of the very long chain polyunsaturated fatty acid on the glycerol backbone. The analysis was based on the formation of various diacylglycerol species from human milk TAG upon chemical (Grignard degradation) or enzymatic degradation. The structure of the TAG was subsequently deduced from data obtained by gas chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
3
6

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(122 citation statements)
references
References 50 publications
7
106
3
6
Order By: Relevance
“…Therefore, the carbon chain length (between 10 and 16 carbons) seems to be a discriminating factor in the distribution of these saturated fatty acids in the sn-2 position of the triacylglycerides. Similar results were found by Martin et al, (1993). Moreover, this increase was observed in C 18 fatty acids, in which we found that relative percentages of these fatty acids in the sn-2 position increased from C18:0 to C18:3 n-3.…”
Section: Fatty Acid Composition Of Infant Formulassupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, the carbon chain length (between 10 and 16 carbons) seems to be a discriminating factor in the distribution of these saturated fatty acids in the sn-2 position of the triacylglycerides. Similar results were found by Martin et al, (1993). Moreover, this increase was observed in C 18 fatty acids, in which we found that relative percentages of these fatty acids in the sn-2 position increased from C18:0 to C18:3 n-3.…”
Section: Fatty Acid Composition Of Infant Formulassupporting
confidence: 90%
“…The reason for this can be explained easily through an example. If we compared our result of sn-2 palmitic acid in mature milk (52.30%) with other studies (Martin et al, 1993;Nelson & Innis, 1999), our result was consistent with that of Martin et al, (51.22%), but was different from the result of Nelson and Innis (56.4%). The error is that we were comparing percentages of sn-2 palmitic acid, but without taking into account the total percentage of palmitic acid in human milk, which varies in Fatty acids and sn-2 fatty acids in human milk A López-López et al the studies.…”
Section: Fatty Acid Composition Of Infant Formulassupporting
confidence: 88%
See 1 more Smart Citation
“…40 . Para a gordura do leite humano, os esferulitos podem corresponder à forma polimórfica β, pois o alto nível de ácido palmítico na posição sn-2 da gordura do leite 35,39,42 torna os triacilgliceróis com estrutura molecular homogênena. Por outro lado, os esferulitos do Betapol mostraram-se opticamente ativos ("axial crosses"), que possivelmente representam cristalização na forma polimórfica β-prima, pois o produto Betapol apresenta alto teor de ácido láurico, o que torna os triacilgliceróis com estrutura molecular mais heterogênea.…”
Section: Propriedades Físico-químicas Da Gordura Do Leite Humano E Dounclassified
“…110,111 Cerca de 87% do DHA encontrado no leite humano está na forma de triacilgliceróis, sendo principalmente esterificado nas posições sn-2 (∼50%) e sn-3 (∼42%) dos triacilgliceróis. 112 Quando lactentes recebem dietas contendo altos teores de DHA, esse ácido graxo tem seu aumento refletido no leite humano, [113][114][115] e proporciona melhor desenvolvimento do sistema nervoso do recém-nascido.…”
Section: Aspecto Funcional Dos Lipídios Estruturados Sucedâneos Da Gounclassified